Faktor – Faktor Pengaruh Tax Avoidance Pada Perusahaan Sektor Barang Konsumen Non – Primer Di BEI Tahun 2018 - 2021 - Aurellia Iinaas Prihandari; Cahyani Nuswandari (Journal of Economic, Bussines and Accounting (COSTING), 2023)
Tax avoidance (tax avoidance) is an effort made by companies to obtain benefits, namely reducing the amount of tax payable in a legal way by exploiting weaknesses in tax regulations.This study aims to find empirical evidence and analyze the effect of capital intensity, thin capitalization and political connections on tax avoidance. The data in this study used financial report data and annual reports for Consumer non – cyclicals listed on the Indonesia Stock Exchange for 2018 – 2021. The sampling method in this study used a purposive sampling technique. The number of samples in this study obtained as many as 238 sample companies. This study was analyzed using multiple linear regression. The test results show that capital intensity has a significant negative effect on tax avoidance, thin capitalization has no effect on tax avoidance and political connections have a significant positive effect. Keywords : Tax Avoidance, Capital Intensity, Thin Capitalization, Political Connection